Implementation of Planned Happenstance In Career Planning and Decision Making - Adha, Idyana; Afdal, Afdal; Hariko, Rezki (Universitas Trunojoyo Madura, 2025)
This article explores the implementation of Planned Happenstance in career planning and decision making. Planned Happenstance is an approach that recognizes the role of serendipity in career journeys and teaches individuals to leverage unexpected opportunities. The discussion in this article covers the concept of Planned Happenstance, its core components, and practical strategies for career planning. In career planning, Planned Happenstance emphasizes the importance of flexibility, adaptability, and preparedness for planned risk-taking. The core components of Planned Happenstance include sustained curiosity, preparedness to seize opportunities, networking skills, adaptability, and learning from experience. Case studies and practical examples presented in this article illustrate how Planned Happenstance can be applied in career planning. These stories provide real-life insights into how individuals use the concept of Planned Happenstance to explore desired industries, engage in planned risk-taking, build effective social networks, learn from experiences, and achieve significant career growth. In implementing Planned Happenstance, individuals need to maintain openness to new opportunities, develop adaptability skills, build strong social networks, and learn from every experience. Through this approach, individuals can leverage uncertainty to attain sustainable career success. This article underscores the significance of Planned Happenstance in navigating the dynamic and complex world of work. By adopting a proactive, flexible, and strategically planned approach to risk-taking, individuals can create unexpected opportunities and achieve remarkable success in their career journeys